Pastoral Care as a Narrative "Offer of Experience": Reflections on Future Testimony of Christianity - Loffeld, Jan (NTT, 2025)
In countries such as the Netherlands and Germany, international religious research shows that religion as a system of meaning is increasingly being forgotten and that its transcendent dimension is failing. At the same time, it becomes apparent how contemporary cultures are getting an increasingly strong narrative basic structure in the sense that questions of life or other essential accomplishments are dealt with narratively (for example in social media). As international cognitive research also shows, the human being seems to be a narrative being. The present article therefore proposes to take this basic narrative structure into account more clearly in pastoral care as well, by trying to interweave the small stories of people today with the great history of the Gospel.